Self-assembled Co3O4 nanostructure with controllable morphology towards high performance anode for lithium ion batteries. (10th January 2016) - Zhang, Yiqiong; Wu, Yiwen; Chu, Yinghong; Li, Lin; Yu, Qipeng; Zhu, Yanfei; Liu, Gang; Hou, Qiong; Zeng, Ronghua; Zhao, Lingzhi
Graphical abstract: The different Co3 O4 nanostructures with controllable morphology are facile obtained through adjusting hydrothermal reaction. The mesoporous nanowires to mesoporous nanoflakes are directly grew on nickel foam when temperatures are increased from 90 °C to 120 °C. Both Co3 O4 nanostructures demonstrate excellent electrochemical performance. Highlights: The different Co3 O4 nanostructures with controllable morphology are facile synthesized through adjusting reaction temperature. Mesoporous Co3 O4 nanoflakes exhibits superior performance in terms of rate capability and cycle stability. Co3 O4 nanostructure grown directly grown on nickel foam enables fast charge transfer pathways, and the highly porous Co3 O4 with high specific surface area facilitates lithium storage. Abstract: The synthesis of Co3 O4 nanostructures with controllable morphology through hydrothermal reaction was investigated. Through adjusting the reaction temperature, mesoporous nanowires (Co3 O4 -NWs) and mesoporous nanoflakes (Co3 O4 -NFs) can be directly grown on nickel foam at a reaction of temperature of 90 °C and 120 °C, respectively. Compared with Co3 O4 -NWs, Co3 O4 -NFs displays greatly improved performance of cyclic stability and rate capability. After 100 cycles, an outstanding reversible capacity of 1300 mAh g −1 with negligible capacity fading is achieved at current density of 100 mA g −1 for Co3 O4 -NFs. Furthermore, Co3 O4 -NFs exhibit excellent rate capability, with a reversible capacity up to ∼450 mAh g −1 even at a current density as high as 8 A g −1 . Due to the directly growing aligned Co3 O4 nanoflakes on conductive 3D nickel foam, the Co3 O4 -NFs electrode shows superior electrochemical performance, with potential as a promising anode candidate for lithium ion batteries.